Chronobiologiceskaja i psichofiziologicheskaja charakteristika funkcional'nogo sostojanija sportsmenov razlicnych specializacij - Pogadaeva, O. V.; Krikucha, Ju.; Tristan, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this paper was to present the chronobiological and psychophysiological characteristic of the functional condition of athletes of various specializations (sports single combats, cyclic and game kinds, gymnastics). Changes of psychophysiological conditions of athletes were estimated with the help of Scondi's projective test, the chronobiological estimation of representations about perception of time was studied also. The results of researches have shown, that women have more exact perception of time characteristics of people around them at the presence of the highest level of personal discomposes, with the aspiration to the authority, the presence of enthusiasm and the display of the greater activity and enterprise down to the aggression. The sports specialization and the level of motor activity have the smaller influence on the functional condition of women in comparison with men.